1966
DOI: 10.1111/j.1476-5381.1966.tb01666.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Drugs on Human Umbilical Artery in Vitro

Abstract: Investigation of the actions of drugs on vascular smooth muscle is frequently complicated by indirect actions mediated through neural elements. However, valuable information on the direct actions of drugs on vascular smooth muscle can often be obtained from experiments on nerve-free preparations. Perfused placental vessels (von Euler, 1938;Panigel, 1962), spirally cut umbilical arterial and venous strips (Somlyo, Woo & Somlyo, 1965), chick amniotic membrane (Ferguson, 1940;Cuthbert, 1963), and rabbit ear vesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

1968
1968
1998
1998

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…2O~22 Only one study mentions a transient dilation followed by a constriction after the addition of histamine to perfused umbilical arteries. 23 In our tests, no relaxation effect could be obtained with histamine on umbilical preparations mounted for isometric tension recording in the presence or absence of indomethacin and contracted with serotonin. However, Clymann et al 24 reported marked increases in cGMP levels in the human umbilical arteries in response to low concentrations of histamine, an effect that is also mediated by an H,-receptor mechanism, while they obtained only moderate increases in cGMP in response to serotonin and acetylcholine at high concentrations.…”
mentioning
confidence: 50%
“…2O~22 Only one study mentions a transient dilation followed by a constriction after the addition of histamine to perfused umbilical arteries. 23 In our tests, no relaxation effect could be obtained with histamine on umbilical preparations mounted for isometric tension recording in the presence or absence of indomethacin and contracted with serotonin. However, Clymann et al 24 reported marked increases in cGMP levels in the human umbilical arteries in response to low concentrations of histamine, an effect that is also mediated by an H,-receptor mechanism, while they obtained only moderate increases in cGMP in response to serotonin and acetylcholine at high concentrations.…”
mentioning
confidence: 50%
“…Part of these relaxations was due to activation of sympathetic nerves followed by excitation of a-adrenoceptors, for they were shortened by antagonists of a-adrenoceptors, adrenergic neurone blocking agents or by tetrodotoxin. Vasodilatation resulting from excitation of a-adrenoceptors by noradrenaline has been described (Gokhale, Gulati, Kelkar & Kelkar, 1966), but we were only able to induce pure relaxations with noradrenaline after a-adrenoceptor block. Relaxations following contractions induced by noradrenaline were occasionally seen, but the loss of tone was prolonged and recovery to the initial resting tone often took 30 min.…”
Section: Discussionmentioning
confidence: 71%
“…the release of noradrenaline and the amplitude of the excitatory junctional potential are both reduced by low concentrations of acetylcholine (Steinsland, Furchgott & Kirpekar, 1973;Vanhoutte, Lorenz & Tyce, 1973;Vanhoutte, 1976;Kuriyama & Suzuki, 1981). However, in addition to their presence on sympathetic nerve endings, both excitatory and inhibitory muscarinic receptors occur elsewhere in blood vessels: contraction to acetylcholine has often been reported for the smooth muscle of larger blood vessels (Furchgott, 1955) and these include non-innervated umbilical arteries (Gokhale, Gulati, Kelkar & Kelkar, 1966) which implies a direct action. Relaxation has been described in a number of arteries (Kuriyama & Suzuki, 1978;Furchgott & Zawadzki, 1980;Takata, 1980).…”
Section: Introductionmentioning
confidence: 99%